Parthenolide regulates oxidative stress‐induced mitophagy and suppresses apoptosis through p53 signaling pathway in C2C12 myoblasts. Issue 9 (29th May 2019) - Ren, Yinghui; Li, Yan; Lv, Jienv; Guo, Xiangdong; Zhang, Jieyou; Zhou, Dongmei; Zhang, Zimu; Xue, Zhenyi; Yang, Guangze; Xi, Qing; Liu, Hongkun; Liu, Zehan; et al.
Abstract: Muscle redox disturbances and oxidative stress have emerged as a common pathogenetic mechanism and potential therapeutic intervention in some muscle diseases. Parthenolide (PTL), a sesquiterpene lactone found in large amounts in the leaves of feverfew, possesses anti‐inflammatory, anti‐migraine, and anticancer properties. Although PTL was reported to alleviate cancer cachexia and improve skeletal muscle characteristics in a cancer cachexia model, its actions on oxidative stress‐induced damage in C2C12 myoblasts have not been reported and the regulatory mechanisms have not yet been defined. In our study, PTL attenuated H2 O2 ‐induced growth inhibition and morphological changes. Furthermore, PTL exhibited scavenging activity against reactive oxygen species and protected C2C12 cells from apoptosis in response to H2 O2 . Meanwhile, PTL suppressed collapse of the mitochondrial membrane potential, thereby contributing to normalizing H2 O2 ‐induced autophagy flux and mitophagy, correlating with inhibiting degradation of mitochondrial marker protein TIM23, the increase in LC3‐II expression and the reduction of mitochondria DNA. Besides its protective effect on mitochondria, PTL also prevented H2 O2 ‐induced lysosomes damage in C2C12 cells. In addition, the phosphorylation of p53, cathepsin B, and Bax/Bcl‐2 protein levels, and the translocation of Bax from the cytosol to mitochondria induced by H2 O2 in C2C12 cells was significantly reduced by PTL. In conclusion, PTL modulates oxidative stress‐induced mitophagy and protects C2C12 myoblasts against apoptosis, suggesting a potential protective effect against oxidative stress‐associated skeletal muscle diseases. Abstract : Parthenolide exhibits a protective effect against oxidative stress by eliminating reactive oxygen species overproduction. Parthenolide suppresses mitochondrial membrane depolarization and inhibits H2 O2 ‐induced autophagy flux and mitophagy. Parthenolide prevents H2 O2 ‐induced lysosomes damage in C2C12 cells. Parthenolide suppresses the H2O2‐induced C2C12 cells apoptosis through inhibition of the activation of p53.